Plasmablast‐like Phenotype Among Antigen‐Experienced CXCR5–CD19low B Cells in Systemic Lupus Erythematosus. Issue 9 (2nd August 2022) - Szelinski, Franziska; Stefanski, Ana Luisa; Schrezenmeier, Eva; Rincon‐Arevalo, Hector; Wiedemann, Annika; Reiter, Karin; Ritter, Jacob; Lettau, Marie; Dang, Van Duc; Fuchs, Sebastian; Frei, Andreas P.; Alexander, Tobias; et al.
Abstract : Objective: Altered composition of the B cell compartment in the pathogenesis of systemic lupus erythematosus (SLE) is characterized by expanded plasmablast and IgD–CD27– double‐negative B cell populations. Previous studies showed that double‐negative B cells represent a heterogeneous subset, and further characterization is needed. Methods: We analyzed 2 independent cohorts of healthy donors and SLE patients, using a combined approach of flow cytometry (for 16 healthy donors and 28 SLE patients) and mass cytometry (for 18 healthy donors and 24 SLE patients) and targeted RNA‐Seq analysis. To compare B cell subset formation during the acute immune response versus that during autoimmune disease, we investigated healthy donors at various time points after receipt of the BNT162b2 messenger RNA COVID‐19 vaccine and patients with acute SARS–CoV‐2 infection, using flow cytometry. Results: We found that IgD–CD27+ switched and atypical IgD–CD27– memory B cells, the levels of which were increased in SLE patients, represented heterogeneous populations composed of 3 different subsets each. CXCR5+CD19 intermediate, CXCR5–CD19 high, and CXCR5–CD19 low populations were found in the switched memory and double‐negative compartments, suggesting the relatedness of IgD–CD27+ and IgD–CD27– B cells. We characterized a hitherto unknown and antigen‐experienced CXCR5–CD19 low subset that was enhanced in SLE patients, had a plasmablast phenotype with diminished B cell receptor responsiveness, and expressed CD38, CD95, CD71, PRDM1, XBP1, and IRF4 . Levels of CXCR5–CD19 low subsets were increased and correlated with plasmablast frequencies in SLE patients and in healthy donors who received BNT162b2, suggesting their interrelationship and contribution to plasmacytosis. The detection of CXCR5–CD19 low B cells among both CD27+ and CD27– populations calls into question the role of CD27 as a reliable marker of B cell differentiation. Conclusion: Our data suggest that CXCR5–CD19 low B cells are precursors of plasmablasts. Thus, cotargeting this subset may have therapeutic value in SLE.